2016
DOI: 10.1007/s10856-015-5663-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in rat organs implanted with endodontic repair materials by ICP-MS

Abstract: To investigate the levels of seven elements using an inductively coupled plasma-mass spectrometry (ICP-MS) method in rat organs after the implantation of Micro Mega Mineral Trioxide Aggregate (MM-MTA), Bioaggregate (BA) and Biodentine (BD) materials. MM-MTA, BA and BD were implanted into the subcutaneous tissue of 15 Wistar albino rats; three control animals had no operation. After 45 days, the rats were sacrificed and their brains, kidneys and livers were removed. The ICP-MS analysis was used to determine tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 29 publications
0
39
1
4
Order By: Relevance
“…In addition, difference in the biocompatibility between both MTA materials on day 7 (Shahi et al 2006) could be associated with the higher concentration of metallic oxide in GMTA (Asgary et al 2006), which interferes with ionic dissociation. Investigations also revealed that the level of trace metal ions from MTA increased in the organs, such as liver, in rats (Demirkaya et al 2016, Simsek et al 2016. Investigations also revealed that the level of trace metal ions from MTA increased in the organs, such as liver, in rats (Demirkaya et al 2016, Simsek et al 2016.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In addition, difference in the biocompatibility between both MTA materials on day 7 (Shahi et al 2006) could be associated with the higher concentration of metallic oxide in GMTA (Asgary et al 2006), which interferes with ionic dissociation. Investigations also revealed that the level of trace metal ions from MTA increased in the organs, such as liver, in rats (Demirkaya et al 2016, Simsek et al 2016. Investigations also revealed that the level of trace metal ions from MTA increased in the organs, such as liver, in rats (Demirkaya et al 2016, Simsek et al 2016.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, the serum calcium levels of both the MTA groups were higher than that of the control group on day 7, while it decreased on day 30. Traces of Ca 2+ released from the MTA have been detected in organs such as the liver, kidney and brain (Simsek et al 2016). The results revealed higher Ca 2+ release during the initial period, followed by subsequent reduction with time (De Vasconcelos et al 2009).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations